Estudio de rentabilidad en la producción de 100 hectáreas de madera teca en la parroquia Saracay provincia de el Oro Ecuador - Chan Mora, Javier Orlando (2014)
This work was made by titration in Saracay Piñas Parish belonging to the canton of the province of El Oro where the profitability of the production of 100 hectares of teak wood was determined, in which the objectives of determining the profitability of established Teak planting and establishing the Cost-Benefit ratio, which were resolved given to a methodology applied to the requirements for crop establishment, studying the different variables that are incurred for the production which were: Supply, Demand, Technology profitability, Investment costs and the resolution of each variable determined the return generated on the exploitation of teak. Besides the market study determined the viability of the culture, maintaining a steady growth in terms of crop area and there agencies that are responsible for the purchase of the final product as it is wood, which also evidenced that Ecuador is an exporter of Teak and consumption in importing countries is increasing. Technical and technological requirements posed in the study were for more technical exploitation of teak and obtain higher production yields, for which a basis of 1 ha, culture teak which we proceeded to estimate the costs line was maintained total investment and the perceived profitability of teak production. So profitability is significant but due to time of cultivation makes it unattractive investment in this business, establishing it as a culture of long-term profits for future generations; where the requirements for planting are not particularly relevant and easily accessible to the establishment of such production.